PENERAPAN PERMAINAN TRADISIONAL CUBLAK-CUBLAK SUWENG UNTUK MENGEMBANGKAN PERILAKU SOSIAL EMOSIONAL ANAK - Fachrurrazi, Ahmad; Anggreni, Made Ayu; Aslifah, Feni Putri (incrementapedia, 2019)
This study is motivated by the state of the school environment that is lacking in the development ofemotional social behavior through traditional games. Children's opportunities to play together in the yardare lacking so that emotional social behavior is not well developed. Developing children's emotionalsocial behavior can be done through playing traditional games one of them game cublak-cublak suweng.This type of research uses Pre-Experimental Design. The design used is One-Group Pretest-PostestDesign, with the subjects taken are 15 children. Data analysis applied in this research is different testtechnique of pre-test and post-test (t-test) from observation of children activity to know the development ofemotional social behavior through traditional game cublak-cublak suweng.The result of data analysisshows the value of Ã°Ââ€˜Â¡Ã¢â€žÅ½Ã°Ââ€˜â€“Ã°Ââ€˜Â¡Ã°Ââ€˜Â¢Ã°Ââ€˜â€ºÃ°Ââ€˜â€21,24 and Ã°Ââ€˜Â¡Ã°Ââ€˜Â¡Ã°Ââ€˜Å½Ã°Ââ€˜ÂÃ°Ââ€˜â€™Ã°Ââ€˜â„¢ 1,76 at ÃŽÂ± 0,05 and 2,62 at ÃŽÂ± 0,01. Then Ã°Ââ€˜Â¡Ã¢â€žÅ½Ã°Ââ€˜â€“Ã°Ââ€˜Â¡Ã°Ââ€˜Â¢Ã°Ââ€˜â€ºÃ°Ââ€˜â€Ã‹Æ’ Ã°Ââ€˜Â¡Ã°Ââ€˜Â¡Ã°Ââ€˜Å½Ã°Ââ€˜ÂÃ°Ââ€˜â€™Ã°Ââ€˜â„¢ so thatÃ°ÂÂÂ»0 is rejected and Ã°ÂÂÂ»1 accepted.